Impact analysis on utilization of telecenter: The case of telecentre in Baling - Hassan, Syahida; Yusof, Yuhanis; Abu Seman, Mohamad Amir; Sheik Osman, Wan Rozaini (2010)
The telecentre in Baling is established under the Universal Service Provision fund, aiming to provide community with broadband access and training programme focusing on e-application. Nevertheless, the impact of this initiative is yet to be studied. Thus,the undertaken study is aimed at examining the utilization and impact of Baling telecentre on the community. A total of 34 respondents were interviewed using structured questionnaires. Outcome of the study indicates that the telecentre has improved its community in certain senses. Lesson learned from the study is also discussed.